Ung medvirkning (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
How should we go about collaborating with children and adolescents? Young Participation: Creativity and Conflict in Planning explores how youth participation work in practical terms, in the context of urban development processes at the municipal level in Norway.